Respuesta :

Answer:

x=-4

Step-by-step explanation:

−3(7−2x)+3=8x−10

Step 1: Simplify both sides of the equation.

−3(7−2x)+3=8x−10

(−3)(7)+(−3)(−2x)+3=8x+−10(Distribute)

−21+6x+3=8x+−10

(6x)+(−21+3)=8x−10(Combine Like Terms)

6x+−18=8x−10

6x−18=8x−10

Step 2: Subtract 8x from both sides.

6x−18−8x=8x−10−8x

−2x−18=−10

Step 3: Add 18 to both sides.

−2x−18+18=−10+18

−2x=8

Step 4: Divide both sides by -2.

−2x

−2

=

8

−2

x=−4

Answer:

-4

Step-by-step explanation:

Step 1: Simplify both sides of the equation.

−3(7−2x)+3=8x−10

(−3)(7)+(−3)(−2x)+3=8x+−10(Distribute)

−21+6x+3=8x+−10

(6x)+(−21+3)=8x−10(Combine Like Terms)

6x+−18=8x−10

6x−18=8x−10

Step 2: Subtract 8x from both sides.

6x−18−8x=8x−10−8x

−2x−18=−10

Step 3: Add 18 to both sides.

−2x−18+18=−10+18

−2x=8

Step 4: Divide both sides by -2.